Laboratory evaluation of micro and nano eggshell powder on physical and rheological properties of bitumen - Zghair Chfat, Alattafi Hadi; Haryati, Yaacob; Nurul Hidayah, Mohd Kamaruddin; Al-Saffar, Zaid Hazim; Putra Jaya, Ramadhansyah (Elsevier Ltd, 2025)
Bitumen is a non-renewable resource, and the rising global demand for it has resulted in higher costs for it. Consequently, researchers have conducted numerous studies exploring sustainable and cost-effective alternatives. One potential solution involves using waste materials as replacements or additives, which offers a promising approach to addressing these challenges. Therefore, this study focused on using eggshell powder in micro-sized (ESP) and nano-sized (NESP) as a modifier for bitumen, aiming to identify the most effective option. The characteristics of bitumen containing ESP and NESP at concentrations of 0 %, 5 %, 7 %, and 9 % by weight of bitumen have been investigated in terms of physical and rheological properties, including penetration, softening point, ductility, viscosity, storage stability, mass loss, and dynamic shear rheometer (DSR) test. In general, the results showed that adding ESP and NESP reduces penetration, increases softening point and viscosity values, and decreases ductility. NESP demonstrated better performance in terms of storage stability and mass loss at high temperatures. The DSR test revealed that the rutting parameter increased as ESP and NESP concentration increased, respectively. Additionally, NESP showed better enhancement in physical and rheological properties than ESP. Notably, 9% NESP represented the optimal concentration for improving bitumen properties. The study demonstrated that using eggshell waste for bitumen modification is a viable option with significant long-term benefits for both resources and the environment.